(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The problem in this study is whether using the discussion method assisted by poster media can improve student learning outcomes in class IV SDN 5 Telaga, Gorontalo Regency. This study aims to improve student learning outcomes through the discussion method assisted by poster media in class IV SDN 5 Telaga, Gorontalo Regency. This type of research is classroom action research. In the initial observation of students who were able to amount to 8 students or 40%, after the action was carried out in cycle I it became 10 students or 50% who were able, then continued in cycle II students who were able to increase to 17 students or 85%. Based on the results of the study, it can be concluded that through the discussion method assisted by poster media, it can improve the learning outcomes of class IV students at SDN 5 Telaga, Gorontalo Regency